PENGARUH KEGIATAN FINGER PAINTING TERHADAP PENINGKATAN KETERAMPILAN MTORIK HALUS ANAK TUNAGRAHITA SEDANG DI SLB C YPLB BANDUNG - Elsa Septiani, - (2023)
This research is motivated to improve the fine motor skills of children with moderate mental retardation through finger painting activities which are expected to contribute to improving the fine motor skills of mentally retarded children, especially those related to needs in improving self-development abilities This study used a quantitative approach with the SSR (single subject research) experimental method, with an A-B-A research design, the number of research subjects was one child, where the research was carried out at SLB C YPLB Bandung with class II research subjects with the initials LP. The results showed that before the intervention was given the child's condition could be seen at baseline-1 with a score of 49.33%, then after the intervention was given an increase in score, namely 70.93%, and at baseline-2 the child got a score of 87.00% at baseline- These 2 children get a higher score than before and have achieved the success criteria for increasing the score. This gives an indication by showing the development of fine motor skills in moderate category mentally retarded children, this can be proven by the child being able to button clothes and close the scissors opening on the handle of the scissors. So it can be said that finger painting activities can improve fine motor skills of mentally retarded children in the moderate category in the activity of daily living (ADL), namely buttoning clothes and closing the opening of the scissors on the handle of the scissors. Researchers recommend this finger painting activity for teachers and/or parents to use as a choice of learning activities, to improve the development of fine motor skills of moderately mentally retarded children Keyword: Finger Painting, Fine Motor Skills, Moderate Mental Retardation